Muhammad Asad’s the message of the Qur’an - Ahmad, Nadzrah; Amir, Ahmad Nabil (Kenneth X Robbins, 2022)
This paper presents the principal framework of tafsir (commentary) as outlined by Muhammad Asad in his unmatched translation and commentary on the Qur’an, The Message of the Qur’an. It strives to analyze its underlying method and principles and the idealism and views that impacted his work. The Message advocated rational principle (al-ra’y) based on the teaching of Muhammad ‘Abduh and Sayid Muhammad Rashid Rida in Tafsir al-Manar, that brought out dynamism and scientific exposition of the ayah as profoundly developed by Asad in his tafsir: